Spinal Cord Injury After Extremity Surgery in Children With Thoracic Kyphosis. Issue 10 (October 2015) - Pruszczynski, Blazej; Mackenzie, William G; Rogers, Kenneth; White, Klane K.
Abstract: Background: Spinal cord injury is a rare complication after lower extremity surgery in children with skeletal dysplasia and thoracic kyphosis. We encountered two patients who had this complication, from among 51 (39 from Nemours/Alfred I. duPont Hospital for Children and 12 from Seattle Children's Hospital) who underwent lower extremity surgery during an 8.5‐year period (June 2004 to December 2012). Because spinal cord injury is a devastating complication likely not known to most physicians treating patients with skeletal dysplasias, we sought to examine factors that may contribute to this rare complication. Case Description: We performed a retrospective review of two patients with skeletal dysplasia who had paraplegia develop after extremity surgery. Outcome measures included operative time, vital signs, and postsurgery recovery of neurologic deficit. MR images were reviewed. Two patients were found—an 8.5‐year‐old boy with spondyloepiphyseal dysplasia congenita with a 76°‐thoracic kyphosis apex at T4 and a 6.5‐year‐old boy with mucopolysaccharidosis type 1‐H with an 80°‐thoracic kyphosis apex at T2. Bilateral proximal femoral osteotomies or bilateral innominate and proximal femoral osteotomies had been performed. The spinal cord injuries occurred at the apex of the kyphosis as determined by clinical examination and MRI assessment. In both patients, the mean arterial blood pressure decreased below 50 mm Hg and might be a factor in the etiology of the paralysis. The first patient recovered motor function in 5 months; the second had no recovery. Literature Review: Paraplegia is extremely rare after nonspine operations. Many factors contribute to the risk for a spinal cord event: low mean arterial pressure, duration of the surgery, position on the operating table, the kyphotic spine deformity, or unappreciated vascular disease. Motor‐evoked potentials and somatosensory‐evoked potentials together potentially provide high sensitivity and specificity for predicting a postoperative neurologic deficit. Clinical Relevance: Based on our two patients with skeletal dysplasia and a literature review of patients with hyperkyphosis undergoing extremity surgery, the surgeon must be aware of the risk of spinal cord injury. Careful preoperative assessment possibly including MRI of the spine is recommended. Mean arterial pressure should be maintained at a safe level; neuromonitoring should be considered.